Respuesta :
Answer:
Step-by-step explanation:
First equation: 2x^2 + 6x = 0 factors into 2x(x + 3) = 0, so either x = 0 or x = -3.
Second equation: x^2 + 9x + 14 = 0 factors into (x + 2)(x + 7) = 0. Thus, either x = -2 or x = -7
Hi there! Hopefully this helps!
---------------------------------------------------------------------------------------------------------
Answer for [tex]2x^{2} + 6x = 0[/tex]:
x = 0
x = -3
|
|[tex]2x^{2} + 6x = 0[/tex]
|
|First we factor out x
\/
[tex]x(2x+6)=0[/tex]
To find equation solutions, solve [tex]x = 0[/tex] and [tex]2x+6 = 0[/tex]
|
\/
[tex]x = 0[/tex]
[tex]x = -3[/tex]
~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~
Answer for [tex]x^{2}+ 9x + 14 = 0[/tex]:
x = -2
x = -7
|
|
|[tex]x^{2}+ 9x + 14 = 0[/tex]
|
|To solve the equation, factor [tex]x^{2}+ 9x + 14[/tex] using formula [tex]x^{2} + (a + b)x + ab = (x+a) (x+b).[/tex] To find [tex]a[/tex] and [tex]b[/tex], set up a system to be solved.
|
\/
[tex]a + b = 9[/tex]
[tex]ab = 14[/tex]
|
\/
Since [tex]ab[/tex] is positive, [tex]a[/tex] and [tex]b[/tex] have the same sign. Since [tex]a + b[/tex] is positive, [tex]a[/tex] and [tex]b[/tex] are both positive. List all such integer pairs that give product 14.
1, 14
2, 7
|
\/
Calculate the sum for each pair.
1 + 14 = 15
2 + 7 = 9
|
\/
The solution is the pair that gives sum 9.
[tex]a = 2[/tex]
[tex]b = 7[/tex].
|
\/
Rewrite factored expression [tex](x+a)(x+b)[/tex] using the obtained values.
[tex](x+2)(x+7)[/tex]
|
\/
To find equation solutions, solve [tex]x + 2 = 0[/tex] and [tex]x + 7 = 0[/tex].
|
\/
[tex]x = -2[/tex]
[tex]x = -7[/tex]